Short Communication Brain: A Mysterious Organ - Shams Raza Brohi, Muzamil Dilber, Hyder Raza Shah (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2012)
Commentary with historical perspective: The brain has always remained a mystery. In 335 B.C. Aristotle thought heart as source of thoughts and sensations; and brain as a radiatior for cooling, The skull was considered as a place of demons. Excavations had showed skull with trephines made for removing demons and bad spirits.